1992
DOI: 10.1111/j.1432-1033.1992.tb17340.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic cleavage of atrial natriuretic factor receptor in bovine adrenal membranes by endogenous metalloendopeptidase

Abstract: Atrial natriuretic factor (ANF) is a peptide hormone from the heart atrium with potent natriuretic and vasorelaxant activities. The natriuretic activity of ANF is, in part, mediated through the adrenal gland, where binding of ANF to the 130-kDa ANF receptor causes suppression of aldosterone secretion. Incubation of bovine adrenal membranes at pH (5.6 caused a rapid and spontaneous cleavage of the 130-kDa ANF receptor, yielding a 65-kDa polypeptide that could be detected by photoaffinity labeling by 1251-labele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Interestingly, the human hippocampus of Alzheimer's disease patients shows increased levels of pro-MMP-9 near the amyloid plaques (Backstrom et al, 1996) and the same increase was reported in amyloidpositive beagle brains (Lim et al, 1997). In addition, levels of circulating MMP-9 are significantly elevated in the plasma of Alzheimer's disease patients compared (Parvathy et al, 1997) Batimastat (BB-94) Broad spectrum MMP and TACE TAPI-2 Zn 2+ -dependent MP TAPI (-1) Collagenase, gelatinase, ADAM-10, TACE (Schwager et al, 1998;Schwager et al, 1999) ANF-R / EDTA MP (Abe and Misono, 1992) AR / Batimastat (BB-94) Broad spectrum MMP and TACE (Vecchi et al, 1998;Brown et al, 1998 MMP-1, MMP-8 > MMP-9 > MMP-3 Not inhibited by TAPI(-1) EGF / EDTA, EGTA MP (Dempsey et al, 1997) Batimastat (BB-94) Broad spectrum MMP and TACE FcyRIII CD16 GI5402 MMP-1,-3,-9,-13 and TACE (Dekkers et al, 2000) O-phen MP (Bazil and Strominger, 1994) (Galon et al, 1998) RU36156 MMP-8, MMP-9 and TACE (Galon et al, 1998;Mota et al, 2004) 168 B. Cauwe et al …”
Section: Figure 17 Differential Cell Surface Proteolysis Of App and Amentioning
confidence: 52%
“…Interestingly, the human hippocampus of Alzheimer's disease patients shows increased levels of pro-MMP-9 near the amyloid plaques (Backstrom et al, 1996) and the same increase was reported in amyloidpositive beagle brains (Lim et al, 1997). In addition, levels of circulating MMP-9 are significantly elevated in the plasma of Alzheimer's disease patients compared (Parvathy et al, 1997) Batimastat (BB-94) Broad spectrum MMP and TACE TAPI-2 Zn 2+ -dependent MP TAPI (-1) Collagenase, gelatinase, ADAM-10, TACE (Schwager et al, 1998;Schwager et al, 1999) ANF-R / EDTA MP (Abe and Misono, 1992) AR / Batimastat (BB-94) Broad spectrum MMP and TACE (Vecchi et al, 1998;Brown et al, 1998 MMP-1, MMP-8 > MMP-9 > MMP-3 Not inhibited by TAPI(-1) EGF / EDTA, EGTA MP (Dempsey et al, 1997) Batimastat (BB-94) Broad spectrum MMP and TACE FcyRIII CD16 GI5402 MMP-1,-3,-9,-13 and TACE (Dekkers et al, 2000) O-phen MP (Bazil and Strominger, 1994) (Galon et al, 1998) RU36156 MMP-8, MMP-9 and TACE (Galon et al, 1998;Mota et al, 2004) 168 B. Cauwe et al …”
Section: Figure 17 Differential Cell Surface Proteolysis Of App and Amentioning
confidence: 52%
“…Similarly, it is possible that Creceptor-like low-molecular-mass receptors previously observed in the adrenal cortex (Meloche at al., 1986a;Shinjo et al, 1986;Takayanagi et al, 1987) and the kidney membranes (Koseki et al, 1986;Hamada et al, 1987) may also have been derived through artificial proteolysis of high-molecular-mass ANF receptors which have been reported by others (Yip et al, 1985;Misono et al, 1985;Meloche et al, 1986b) to be predominant in these organs. Indeed, it was found that the 130-kDa ANF receptor in bovine adrenal cortex membranes was readily cleaved by an endogenous proteasc (Misono, 1988;Abe and Misono, 1992), or by exogenously added trypsin (Liu et al, 1989) to generate an ANFbinding fragment with a molecular mass around 60 kDa. Moreover, the adrenal receptor cleaved by the endogenous protease was found to exhibit C-receptor-like properties, such as relaxed ligand specificity and lack of guanylate cyclase activity (Abe and Misono, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was found that the 130-kDa ANF receptor in bovine adrenal cortex membranes was readily cleaved by an endogenous proteasc (Misono, 1988;Abe and Misono, 1992), or by exogenously added trypsin (Liu et al, 1989) to generate an ANFbinding fragment with a molecular mass around 60 kDa. Moreover, the adrenal receptor cleaved by the endogenous protease was found to exhibit C-receptor-like properties, such as relaxed ligand specificity and lack of guanylate cyclase activity (Abe and Misono, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The ECD contains a highly conserved chloride‐binding site near the ECD dimerization interface [17,18]. The ECD also contains in its juxtamembrane region a highly conserved structural motif, referred to as the receptor‐GC signaling motif [19]. Single‐residue mutations in this motif either render the receptor unresponsive to ligand binding or cause constitutive activation of GC activity [20], suggesting that this conserved structure plays a critical role in transmembrane signal transduction.…”
Section: Natriuretic Peptide Receptors –Molecular Topologymentioning
confidence: 99%